Overcoming pathological gambling: therapist guide - Ladouceur, Robert (Treatments that work, 2007)
Introductory information for therapists -- Pre-treatment assessment -- Behavioral interventions -- Cognitive interventions -- Relapse prevention -- Posttreatment assessment -- Follow-up assessments -- Difficulties related to the treatment